Dopamine in socioecological and evolutionary perspectives: implications for psychiatric disorders - Yamaguchi, Yoshie; Lee, Young-A; Goto, Yukiori (Frontiers in Neuroscience, 2015)
Dopamine (DA) transmission in brain areas such as the prefrontal cortex (PFC) and nucleus accumbens (NAcc) plays important roles in cognitive and affective function. As such, DA deficits have been implicated in a number of psychiatric disorders such as schizophrenia and attention deficit/hyperactivity disorder (ADHD). Accumulating evidence suggests that DA is also involved in social behavior of animals and humans. Although most animals organize and live in social groups, how the DA system functions in such social groups of animals, and its dysfunction causes compromises in the groups has remained less understood. Here we propose that alterations of DA signaling and associated genetic variants and behavioral phenotypes, which have been normally considered as "deficits" in investigation at an individual level, may not necessarily yield disadvantages, and even work advantageously, depending on social contexts in subjects with such DA alterations living in social groups. This hypothesis could provide a novel insight into our understanding of the biological mechanisms of psychiatric disorders, and a potential explanation that disadvantageous phenotypes associated with DA deficits in psychiatric disorders have remained in humans through evolution.